Etiology Exploration of Non-alcoholic Fatty Liver Disease From Traditional Chinese Medicine Constitution Perspective: A Cross-Sectional Study - Zhu, Ke; Guo, Yongsong; Zhao, Chenghao; Kang, Shixin; Li, Jialiang; Wang, Jiexin; Tang, Zhaohui; Lin, Bing; Li, Weihong (Frontiers in Public Health, 2021)
Background. The phlegm-dampness constitution might be a key factor in the formation of non-alcoholic fatty liver disease (NAFLD), according to some traditional Chinese medicine (TCM) practitioners’ clinical experience. However, it lacks rigorous statistical evidence. This study aimed to test the association between the phlegm-dampness constitution and NAFLD. Methods. We conducted a cross-sectional study. Participants were residents living in Chengdu, China, undergoing the medical tests at the health management center of Affiliated Hospital of Chengdu University of Traditional Chinese Medicine between December 2018 and September 2020. TCM constitution type was diagnosed by DAOSH four examinations instrument, NAFLD was diagnosed according to the liver ultrasonography and medical history. Multivariate logistic regression and propensity score matching (PSM) were used to analyze a total of 1,677 qualified data. Results. Among 1027 participants with the biased constitution(s), 68.5% had mixed constitutions (with at least two constitutions). Among 703 mixed constitutions participants, compared with the non-phlegm-dampness constitution group, the phlegm-dampness constitution group had a higher proportion of dampness-heat constitution (P=0.005). Among 1677 participants, compared with the non-phlegm-dampness constitution group, the odds ratio (OR) of NAFLD in the phlegm-dampness constitution group was 2.1 in the crude model. After adjusting for age, gender, BMI, other mixed constitutions, smoking, high blood pressure, diabetes, and dyslipidemia, the OR value was reduced to 1.5 (95% confidence interval 1.0 to 2.2, P=0.029). The associations of seven other biased TCM constitutions and NAFLD were not statistically significant in the fully adjusted model. PSM analysis showed consistent results with logistic regression. Conclusions. People tend to have mixed TCM constitutions, and the phlegm-dampness constitution often mixes with the dampness-heat constitution. Among eight biased TCM constitutions, the phlegm-dampness constitution is independently associated with NAFLD. We speculate that TCM phlegm-dampness constitution is a risk factor of NAFLD.